Rekonstruksi Kebijakan Fasilitasi Hukum dan Pendaftaran Merek bagi UMKM Ekonomi Kreatif dalam Rangka Percepatan Pembangunan Ekonomi Daerah - Fatma Afriyani; Ilham Setio Wibowo; Robi Santoso (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, contributing more than 60% to the national GDP and serving as the primary driver of regional economic development. However, the creative economy sector still faces significant challenges, particularly in legal protection for brands and products. Limited understanding of trademark registration, complex administrative processes, and relatively high costs result in many products being legally vulnerable and difficult to compete in wider markets. This study aims to analyze the reconstruction of legal facilitation policies and trademark registration for creative economy MSMEs as a strategy to accelerate regional economic development. Using a normative juridical approach with a statutory and conceptual approach, this research examines the implementation of Law Number 20 of 2016 concerning Marks and Geographical Indications, regional government policies, and their impact on MSME development. The findings indicate that while various facilitation programs have been implemented, their effectiveness is hindered by regulatory synchronization issues, limited budgets, and low digital literacy among MSME actors. This study recommends strengthening regulations through the formation of regional regulations that provide legal certainty, increasing budget allocation for intellectual property rights facilitation, and expanding partnerships with the private sector and higher education institutions.